Marketing Strategy Through Social Media To Improve Sales Achievement Of Msmes In Bengkulu City (Case Study Of Nafoody's Catering) - Arie Nugraha Pratama; Yudi Irawan Abi; Lydia Gustina Putri (Utami Publisher, 2026)
The rapid development of information and communication technology has transformed the way business owners market their products and interact with consumers. For Micro, Small, and Medium Enterprises (MSMEs), social media is not only a promotional tool but also a primary platform for building brand image and increasing sales. This study aims to analyze the marketing strategies implemented by the MSME Catering Nafoody’s through social media and to evaluate their effectiveness in improving sales performance. The research focuses on how Catering Nafoody’s utilizes various social media features such as Instagram, TikTok, Facebook, and WhatsApp Business to expand market reach and strengthen customer relationships.The research method used is a qualitative descriptive approach. Data were collected through in-depth interviews with the owner of Catering Nafoody’s, observations of promotional activities on social media, and documentation in the form of digital content and sales reports. Data analysis was carried out descriptively. The study also reviews elements of digital marketing strategy such as content creation and audience interaction.The results of the study indicate that Catering Nafoody’s marketing strategy focuses on using creative and interactive content to attract consumer attention, such as behind-the-scene production videos, customer testimonials, and collaborations with local micro-influencers. These strategies have been proven to increase the engagement rate on social media accounts and broaden the reach of potential audiences. Another factor supporting the success of this strategy is consistency in promoting products and responsive customer service through direct message features and WhatsApp Business. Overall, the study concludes that the implementation of marketing strategies through social media plays an important role in improving the sales performance of Catering Nafoody’s. Optimizing content, selecting platforms that match the target market, and the ability to adapt to digital trends are key to the success of this strategy. The results of this study are expected to serve as a reference for other MSME actors in developing effective, efficient, and sustainable digital marketing strategies in today’s era of digital transformation.